The Relationship between Maternal Stimulation and the Development of Independence in Preschool Children - Viola Hamnesti; Riri Novayelinda; Ari Rahmat Aziz (Journal of Education Technology Information Social Sciences and Health, 2024)
The development of independence in preschool children (3-6 years) cannot be separated from the role of the family, especially the mother. One of the factors that influence a child's independence is the mother's age, mother's education, mother's occupation, mother's religion and mother's ethnicity. Therefore, this study aims to identify the relationship between maternal stimulation and the development of independence in preschool-aged children. The design of this research is descriptive correlational, the data collection tool is using the Pre-Screening Questionnaire (KPSP), data analysis is univariate and bivariate analysis, the sampling technique used in this research is purposive sampling. The population in this study were all mothers who had preschool age children in Payung Sekaki District, Pekanbaru City. The total sample in this study was 100 respondents. The results of the research were 55 mothers (55%) who received stimulation in the good category and 68 children (68%) who received stimulation in the appropriate category. The chi-square test results obtained p value (0.000) α (0.05), which means that H0 is rejected. It can be concluded that there is a relationship between maternal stimulation and the development of independence in preschool children.